Antihyperglycemic and Anti-Inflammatory Effects of Standardized Curcuma xanthorrhiza Roxb. Extract and Its Active Compound Xanthorrhizol in High-Fat Diet-Induced Obese Mice. (23rd June 2014) - Kim, Mi-Bo; Kim, Changhee; Song, Youngwoo; Hwang, Jae-Kwan
Abstract : Xanthorrhizol, a natural compound isolated from Curcuma xanthorrhiza Roxb. (Java turmeric), has been reported to possess antioxidant and anticancer properties; however, its effects on metabolic disorders remain unknown. The aim of the present study was to evaluate the effects of xanthorrhizol (XAN) and C. xanthorrhiza extract (CXE) with standardized XAN on hyperglycemia and inflammatory markers in high-fat diet- (HFD-) induced obese mice. Treatment with XAN (10 or 25 mg/kg/day) or CXE (50 or 100 mg/kg/day) significantly decreased fasting and postprandial blood glucose levels in HFD-induced obese mice. XAN and CXE treatments also lowered insulin, glucose, free fatty acid (FFA), and triglyceride (TG) levels in serum. Epididymal fat pad and adipocyte size were decreased by high doses of XAN (26.6% and 20.1%) and CXE (25.8% and 22.5%), respectively. XAN and CXE treatment also suppressed the development of fatty liver by decreasing liver fat accumulation. Moreover, XAN and CXE significantly inhibited production of inflammatory cytokines, such as tumor necrosis factor-alpha (TNF- α ), interleukin-6 (IL-6), interleukin-1 β (IL-1 β ), and C-reactive protein (CRP) in adipose tissue (27.8–82.7%), liver (43.9–84.7%), and muscle (65.2–92.5%). Overall, these results suggest that XAN and CXE, with their antihyperglycemic and anti-inflammatory activities, might be used as potent antidiabetic agents for the treatment of type 2 diabetes.